Proximate analysis and chewiness of hydrogen rich water modified sweet potato noodles - Budiarti Gita Indah; Sulistiawati Endah; Kumalasari Ika Dyah (BIO Web of Conferences)
Wheat-based noodles have a high glycemic index, making them unhealthy for diabetics. Hydrogen rich water modified sweet potato noodles can be an alternative to wheat flour. This research aims to find the best proximate and chewiness analysis results. This study used the fixed variable pH hydrogen rich water 9, the ratio of wheat and sweet potato flour 1:1, the independent variable was the type of sweet potato, namely purple sweet potato and yellow sweet potato. The best noodles are obtained from yellow sweet potatoes modified with hydrogen rich water. Proximate value of yellow sweet potato as follows: water content 29.81%, ash 1.525% wb, fat 4.21% wb, total protein (Fk: 6.25) 9.025% wb, carbohydrates by difference 55.43% wb, crude fiber 0.64 % wb, calories 274.98(Cal/100 gr). The chewniess value was higher for yellow sweet potato at 2217.7 N. Yellow sweet potato noodles modified by hydrogen rich water had a higher chewiness value than noodles made from wheat.